Institutional drivers of global value chains participation in African countries - Kadoukpè Gildas Magbondé (Research Network Sustainable Global Supply Chains, 2025)
Despite the expansion of global value chains (GVCs) over the last three decades, African countries trail the other developing regions in terms of GVC integration. Yet, the drivers of African countries' GVC participation are not well understood compared to developed countries. The current paper fills this knowledge gap by providing empirical evidence of the institutional drivers of GVC participation in Africa. It uses the instrumental variable approach based on a panel dataset of 37 African countries spanning the period 2002-2018 to examine the impacts institutions have on total, backward, forward GVCs as well as GVC position. Though no significant effect is recorded with respect to total GVC participation, the instrumental-variable estimates suggest that upgraded institutions encourage backward GVCs and reduce both forward GVCs and upstreamness. For a successful transition from upstream stages of GVCs, African countries must consider strengthening their political and economic institutions.
Keywords: F13; F23; P48; E02; 330; Institutions; global value chains; African countries and instrumental variable approach